2019
DOI: 10.1177/0959354319828174
|View full text |Cite
|
Sign up to set email alerts
|

Encountering the stranger: Hannah Arendt and the shortcomings of empathy as a moral compass

Abstract: It is an often taken for granted notion in contemporary Western everyday life that there is an intimate connection between empathy and moral action. Yet in recent years, this connection has come under scrutiny. In this article, we first ask the question, what is empathy? A brief survey over the psychological and philosophical approaches to the notion of empathy shows that it remains a highly contested concept. The field has a propensity to discuss empathy within the frame of sameness. We instead argue that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This would be to realize the potentials of scholen agein —the free time that was the original purpose of schools. One may “rise up to humanity through culture” (Gadamer, 2000) by entering into a suspended relationship with the world and other people, where the goal is not to develop knowledge in a purely cognitive sense, but rather to engage in imaginative thinking concerned with meaning: “according to Arendt’s theory, moral education should strive to teach pupils to understand the world from multiple perspectives in a continuous, never-ending manner whilst developing their own voice and ability to take responsibility.” (Matthiesen & Klitmøller, 2019, p. 196, p. 196)…”
Section: Thinking As Moral Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…This would be to realize the potentials of scholen agein —the free time that was the original purpose of schools. One may “rise up to humanity through culture” (Gadamer, 2000) by entering into a suspended relationship with the world and other people, where the goal is not to develop knowledge in a purely cognitive sense, but rather to engage in imaginative thinking concerned with meaning: “according to Arendt’s theory, moral education should strive to teach pupils to understand the world from multiple perspectives in a continuous, never-ending manner whilst developing their own voice and ability to take responsibility.” (Matthiesen & Klitmøller, 2019, p. 196, p. 196)…”
Section: Thinking As Moral Educationmentioning
confidence: 99%
“…Arendt celebrates this as something wonderful when the inner dialog leads people to new meaningful insights or simply revolves around treasured memories. As Matthiesen and Klitmøller (2019) explain when quoting Arendt, thinking is not a highly developed intelligence or sophistication, but rather the disposition to live together explicitly with oneself, to have intercourse with oneself, that is, to be engaged in that silent dialog (p. 194). Arendt pays tribute to Socrates, who discovered that one may have a conversational relationship with oneself as well as with others, as he was famous for suddenly falling into spells and seemingly be preoccupied with his own inner life for a long time.…”
Section: Arendt On Thinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Freud (1921) pointed to a decline in personal responsibility and to regressive processes in group dynamics. It has been claimed that empathic response is a culturally scripted norm that is biased towards those who are similar, while overlooking the suffering of particular others (Matthiesen & Klitmøller, 2019). Brain studies have indicated that perceiving others as similar activated the medial prefrontal cortex, whereas its reduced activation was related to dehumanization, that is, to denial of the mental and moral characteristics of others (L. T. Harris & Fiske, 2011;Haslam, 2006;Jack et al, 2013).…”
Section: Orientation To Social Dominancementioning
confidence: 99%